Characteristics and Competencies of Educators in the Technological Era: Literature Review - Okti, Diana Rezu; Solfema, Solfema; Karneli, Yeni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The digital revolution has fundamentally changed the educational landscape, demanding educators to adapt and develop new characteristics and competencies relevant to the technological era. This article presents a comprehensive literature review of the characteristics and competencies of educators in the technological era, focusing on digital skills, innovative teaching methods, and adaptability to technological changes. This research collects and analyzes various literature sources to identify the key components that make up effective educators in the digital context. The results of the study show that educators in the technology era must have the ability to integrate technology into the curriculum, utilize digital tools to increase student interactivity and engagement, and adapt quickly to technological advances. In addition, aspects such as digital literacy, creativity, and critical thinking are becoming increasingly important. The article also discusses the challenges faced by educators, including the digital divide, the need for ongoing training, and resistance to change. The findings of this study provide valuable insights for educators, policymakers, and educational institutions in designing effective professional development strategies and programs to support educators in the technological era